Peran Pemerintah Daerah dalam Penyelesaian Administrasi Pertanahan (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this study is to determine the role of local government in the settlement of land administration. The research method used in this study is a type of empirical legal research. While the approach used is a statutory approach, conceptual approach, case approach, and sociological approach to law. Data collection techniques that researchers use are interviews and document studies. The data that has been collected is then analyzed using descriptive qualitative analysis. As for the results of this study, namely in the practice of legal protection for land administration for the development of public interests, the government protects rights divided into two, namely Preventive Legal Protection and Repressive Legal Protection. Preventive legal protection must be carried out systematically involving several sources who play a role and have authority. Cancellation of Rights is a coercive institution that is used to decide/terminate/abolish the legal relationship between the Owner and his/her land. Furthermore, to realize development both in the regions and at the national level, the function of land is an important element in supporting development. Later during the construction period the supply of land for development projects was very limited. With regard to the taking of people's lands for development purposes, there are two ways taken by the government, namely revocation of land rights (ontoi gening) and land acquisition (prijsgeving)